The Subject Vanishes: Jews, Heretics, and Martyrs after the Linguistic Turn - Fredriksen, Paula (2024)
The “linguistic turn” in early Christian studies, a signal contribution of the work of Elizabeth A. Clark, has raised scholarly awareness of the degree to which terms previously thought to describe social realia in fact function as discursive categories rhetorically deployed for various ends by ancient authors. With this new awareness, how then do we now move from—or work with—our texts’ rhetorical “Jews,” “heretics,” and “martyrs” to recover these ancient historical actors? How does thinking with ideas such as “religion” and “ethnicity,” or with terms such as “paganism,” “Judaism,” and “Christianity,” hinder or help our efforts? How do invocations of “persecution” throughout the first through fifth centuries serve as a dramatic medium for the internal construction of group identity? This essay explores these questions, while raising others about the lures of anachronism and the requirements of narrative for writing history—our own recreation of the past.